Effect of Organic Manures on Seed Germination and Seedling Growth of Khirni - Samir, Malay; Rai, Ratna; Prasad, Birendra (Indian Forester, 2016)
An experiment was conducted to study the effect of organic manures on germination and growth behaviour of khirni seedlings. The experiment comprised of eight media formulated by mixing soil, sand, FYM, vermicompost, poultry manure, cocopeat and spent mushroom compost in different combinations. The study indicated that seed germination and seedling growth parameters of khirni seeds were greatly influenced by the growing media. The results revealed that the combination of Soil + Sand + FYM proved superior in terms of seed germination, seedling length, number of leaves, root length, root dry weight, seedling dry weight, seedling vigour index-l and II whereas greater shoot length, stem diameter and dry weight of shoots were recorded in the media containing Soil+ Sand+ Vermicompost..